Cervical Cancer Screening Among Immigrant Women Residing in Australia: A Systematic Review. (November 2021) - Alam, Zufishan; Shafiee Hanjani, Leila; Dean, Judith; Janda, Monika
Since the introduction of systematic population-based cervical cancer screening in Australia in 1991, age-standardized incidence of cervical cancer has halved. Given recent advances in human papillomavirus (HPV) vaccination and screening, cervical cancer may be eliminated nationally within 20 years. However, immigrant women are not equitably reached by screening efforts. This study systematically reviewed evidence on cervical cancer screening practices among immigrant women in Australia. A systematic search of MEDLINE, Embase, PubMed, CINAHL, and PsycINFO and gray literature for English language studies published till March 1, 2019, was conducted. Observational and qualitative studies evaluating cervical cancer screening awareness and participation of immigrant women were screened. Of 125 potentially relevant studies, 25 were eligible: 16 quantitative (four cohort, 12 cross-sectional), six qualitative, and three mixed-methods studies. Quantitative studies indicated 1% to 16% lower screening rates among migrant women compared with Australian-born women, with participation of South Asian women being significantly lower. Qualitative studies illustrated factors affecting women's willingness to participate in screening, including insufficient knowledge, low-risk perception, and unavailability of a female health professionals being key barriers. Future studies should focus on South Asian women, due to recent increase in their immigration.